Alternative protective garment design specifications for the special operation unit of the Royal Malaysian Police Force / Muhamad Firdaus Ramli - Ramli, Muhamad Firdaus (2016)
A protective garment is essentially important for enforcements personnel member application during the critical employment. In the context of natural and environmental condition, creation of protective garments in tropical climate practice such as ergonomics, mobility, appearance and comfort are among difficulties experienced by Malaysian Police Force (PDRM) on duties. The existing protective design is incomprehensible and became a problem with the movement of enforcement personnel bodies throughout the field operation in crime prevention activity. Therefore, the exploratory research is required to be conducted in this research. The improvements of protective design focused on optimum exploration for effectual protective design interest. In this study, the problem toward artistic exploration was required to enhance the safety protection for the security forces personnel. A research undertaking was conducted on the empirical elaboration of alternative design specifications towards the improvisation of protective garment designs